The Role of Joint Ventures in Northern Bobwhite Conservation - Stephen DeMaso (National Quail Symposium Proceedings, 2017)
Partnerships are crucial part of northern bobwhite (Colinus virginianus) conservation. A key principle is that no single entity can effectively address the complex landscape-level conservation issues to sustain populations and their supporting habitats in perpetuity. Joint Ventures (JVs) use a partnership based approach to deliver specific bird population and habitat objectives within their geography. Currently, 7 of the 12 JVs that occur in the North American bobwhite range have bobwhites listed as a priority species. This presentation will cover various topics including: 1) the history of JVs in North America; 2) an overview of the variety of models used in these partnerships to achieve bird conservation; 3) strategic habitat conservation framework applied to bobwhite conservation within the Gulf Coast Joint Venture; and 4) a discussion of bobwhite conservation products developed by some of the JVs that reside within the bobwhite range in North America.
Keywords: colinus virginianus; northern bobwhite; conservation; population